Comparison of delivery catheter-based and stylet-based right ventricular lead placement at the right ventricular septum under fluoroscopic guidance judged by cardiac CT (Mt. FUJI): a study protocol for the Mt. FUJI randomised controlled trial. Issue 5 (26th May 2021) - Naruse, Yoshihisa; Miyajima, Keisuke; Sugiura, Ryo; Muto, Masahiro; Ogano, Michio; Kurebayashi, Nobutake; Shiozawa, Tomoyuki; Kiyama, Yumi; Nagata, Eiko; Odagiri, Keiichi; Maekawa, Yuichiro
Abstract : Introduction: Pacing-induced cardiomyopathy occasionally occurs in patients undergoing pacemaker implantation. Although compared with right ventricular (RV) apical pacing, RV septal pacing can attenuate left ventricular dyssynchrony; the success rate of lead placement on the RV septum using the stylet system is low. Additionally, no randomised controlled trial has addressed the issue regarding the accuracy of RV lead placement on the RV septum using the stylet and delivery catheter systems. This study hypothesises that a newly available delivery catheter system can improve the accuracy of RV lead placement on the RV septum. Methods and analysis: In a multicentre, prospective, randomised, single-blind, controlled trial, 70 patients with pacemaker indication owing to atrioventricular block will be randomised to either the delivery catheter or stylet group before the pacemaker implantation procedure. The position of the RV lead tip will be assessed using ECG-gated cardiac CT in all patients within 4 weeks after pacemaker implantation. Lead tip positions are classified into three groups: (1) RV septum, (2) anterior/posterior edge of the RV septal wall and (3) RV free wall. The primary endpoint will be the success rate of RV lead tip placement on the RV septum, which will be evaluated using cardiac CT. Ethics and dissemination: This study will be conducted according to the stipulations of the Helsinki Declaration and the institutional review board of Hamamatsu University School of Medicine. The results of the study will be disseminated at several research conferences and will be published in peer-reviewed journals. Trial registration number: jRCTs042200014; Pre-results.